PRINCIPLES OF PUBLIC-PRIVATE PARTNERSHIP APPROACH FOR PROVIDING SUSTAINABLE SOCIAL HOUSING PROJECTS IN NEW EGYPTIAN CITIES (CASE STUDY: EXPERIENCE OF ORASCOM SOCIAL HOUSING PROJECT IN 6 OCTOBER CITY). Issue 2 (2018) - Abd-Elkawy, Abeer Ahmed Mohamed
No abstract available